UV-Induced fingerprint spectroscopy. (30th January 2022) - Nejdl, Lukas; Havlikova, Martina; Mravec, Filip; Vaculovic, Tomas; Faltusova, Veronika; Pavelicova, Kristyna; Baron, Mojmir; Kumsta, Michal; Ondrousek, Vit; Adam, Vojtech; Vaculovicova, Marketa
Highlights: The analytical application of photochemistry is presented in a new light – fingerprinting. Fingerprints were evaluated by a statistical analysis of 1045 wine samples. An easy-to-use, low-cost method with high miniaturization potential was developed. Abstract: Here, we present the potential analytical applications of photochemistry in combination with fluorescence fingerprinting. Our approach analyzes the fluorescence of samples after ultraviolet light (UV) treatment. Especially in presence of metal ions and thiol-containing compounds, the fluorescence behavior changes considerably. The UV-induced reactions (changes) are unique to a given sample composition, resulting in distinct patterns or fingerprints (typically in the 230–600 nm spectral region). This method works without the need for additional chemicals or fluorescent probes, only suitable diluent must be used. The proposed method (UV fingerprinting) suggests the option of recognizing various types of pharmaceuticals, beverages (juices and wines), and other samples within only a few minutes. In some studied samples (e.g. pharmaceuticals), significant changes in fluorescence characteristics (mainly fluorescence intensity) were observed. We believe that the fingerprinting technique can provide an innovative solution for analytical detection.